Modelling and control of offshore crane systems - Raja Mohd Taufika, Raja Ismail (2015)
Cranes are widely used in transportation, construction and manufacturing. Suspended payloads in crane system are caused to swing due to actuator movement, external disturbance such as wind flows, and motion of the crane base in the case of portable cranes. Recently, offshore cranes have become a new trend in stevedoring and in offshore construction as they can help to avoid port congestion and also to exploit ocean engineering applications. For crane operations, it is important to satisfy rigorous requirements in terms of safety, accuracy and efficiency. One of the main challenges in crane operations has been identified as the sway motion control, which is subject to underactuation of crane drive systems and external disturbances. Particularly in offshore cranes, the harsh conditions can produce exogenous disturbances during the load transfer at various scenarios of offshore crane operations in practice. Therefore, it is interesting as to how to design robust controllers to guarantee high performance in the face of disturbances and parameter variations in offshore cranes.